Correction: Perinatal Choline Supplementation Reduces Amyloidosis and Increases Choline Acetyltransferase Expression in the Hippocampus of the APPswePS1dE9 Alzheimer's Disease Model Mice. - Tiffany J Mellott; Olivia M Huleatt; Bethany N Shade; Sarah M Pender; Yi B Liu; Barbara E Slack; Jan K Blusztajn (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0170450.].